2019
DOI: 10.1002/pssr.201900129
|View full text |Cite
|
Sign up to set email alerts
|

Rectified Ion Transport Through 2D Nanofluidic Heterojunctions

Abstract: Nacre-mimetic 2D nanofluidic architectures emerge as a splendid platform for both fundamental research and practical application of the novel ionic and molecular transport phenomena on nano-and sub-nanoscale. So far, it is challenging to endow the 2D nanofluidic systems with asymmetric transport properties and tunable selectivity. Herein, a heterogeneous 2D nanofluidic membrane is fabricated by sequential deposition of negatively and positively charged graphene oxide (GO) nanosheets, and the rectified salt ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…For instance, CVD, ALD, and magnetron sputtering methods were used to prepare single-layer graphene with nanopores [261] or a single sub-nanometer pore, [221][222][223] heterogeneous Al 2 O 3 /SiO 2 nanochannels, [181] and sandwichlike WO 3 /AAO/NiO, [37] respectively. The vacuum filtration approach can be used to construct layered materials (e.g., GO, [61,262] C 3 N 4 , [135] MXene, [136,139] BN, [263] and kaolinite [144] ), I/I (e.g., CaWO 4 /MnO 2 , [68] GO/AAO, [196] and GO/GO [206,[264][265][266] ), O/I (e.g., SNF/AAO [202] and PPSU-Pyx/GO [208] ), and O/O heterogeneous membranes (e.g., TYP-CNF/(PVP/PAN) [210] ). By using the coating method, 3D mesoporous carbon, [165] I/I (e.g., TiO 2 /AAO [67] ), O/I (e.g., BCP/AAO, [186] PI/AAO, [189] and MOF/AAO [153] ), O/O (e.g., BCP/BCP, [192,193] BCP/PET, [190,191,197] and PET/CP [99] ), and O/M heterogeneous membranes (e.g., PC/AuNPs [267] ) can be obtained.…”
Section:  Construction Methods Of Nanochannel-structured Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CVD, ALD, and magnetron sputtering methods were used to prepare single-layer graphene with nanopores [261] or a single sub-nanometer pore, [221][222][223] heterogeneous Al 2 O 3 /SiO 2 nanochannels, [181] and sandwichlike WO 3 /AAO/NiO, [37] respectively. The vacuum filtration approach can be used to construct layered materials (e.g., GO, [61,262] C 3 N 4 , [135] MXene, [136,139] BN, [263] and kaolinite [144] ), I/I (e.g., CaWO 4 /MnO 2 , [68] GO/AAO, [196] and GO/GO [206,[264][265][266] ), O/I (e.g., SNF/AAO [202] and PPSU-Pyx/GO [208] ), and O/O heterogeneous membranes (e.g., TYP-CNF/(PVP/PAN) [210] ). By using the coating method, 3D mesoporous carbon, [165] I/I (e.g., TiO 2 /AAO [67] ), O/I (e.g., BCP/AAO, [186] PI/AAO, [189] and MOF/AAO [153] ), O/O (e.g., BCP/BCP, [192,193] BCP/PET, [190,191,197] and PET/CP [99] ), and O/M heterogeneous membranes (e.g., PC/AuNPs [267] ) can be obtained.…”
Section:  Construction Methods Of Nanochannel-structured Membranesmentioning
confidence: 99%
“…Vacuum filtration Layered membranes (e.g., GO, [61,262] C 3 N 4 , [135] MXene, [136,139] BN, [263] and kaolinite [144] ), I/I (e.g., CaWO 4 /MnO 2 , [68] GO/AAO, [196] and GO/GO [206,[264][265][266] ), O/I (e.g., SNF/AAO [202] and PPSU-Pyx/ GO [208] ), O/O heterogeneous membranes (e.g., TYP-CNF/(PVP/PAN) [210] ) [61,68,135,136,139,144,196,202,206,208,210,[262][263][264][265][266] Coating 3D mesoporous carbon [165] , I/I (e.g., TiO 2 /AAO [67] ), O/I (e.g., BCP/AAO, [186] PI/AAO, [189] and MOF/AAO [153] ), O/O (e.g., BCP/BCP, [192,193] BCP/PET, [190,191,197] and PET/CP [99] ) and O/M heterogeneous membranes (e.g., PC/AuNPs [267] ) [67,99,…”
Section: Top-down Approachmentioning
confidence: 99%
“…During the exfoliation process, large functional groups formed on the nanosheet surfaces during the reactions between layered precursors and strong acids and oxidants, and these functional groups with different dissociation constants (pK a ) caused the nanosheets to exhibit various charge characteristics associated with their protonation and deprotonation in the aqueous environment. [29,[154][155][156] In addition to the ionizable surface groups, isomorphous substitution or bond breaking would also lead to the nanosheets having charged surfaces. Furthermore, as described above, the surfaces of the nanosheets could be modified to further change the original charge state, which may allow for advanced membranes to be developed.…”
Section: Electrostatic Interactionsmentioning
confidence: 99%
“…To date, both the chemical and physical characteristics of the 2D nanochannels, including the surface charge, wetting behavior, and channel morphology and size, can be appropriately adjusted, facilitating the development of higher performance membranes. [28][29][30][31][32] Recently, the scientific community also confirmed that it is feasible to construct heterogeneous lamellar membranes by combining different nanosheets, thus providing more opportunities to explore novel transportation mechanisms based on accurate structural predesign. [33,34] In this Review, we begin with an overview of the basic unit of nanochannel membranes, 2D nanosheets, and the emerging fabrication techniques for homo-and heterolamellar nanoarchitecture construction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation